Lung cancer in patients with pulmonary fibrosis: characteristics features and prognosis - Kara, Sibel; Mogulkoc, Nesrin; Kirkil, Gamze; Cetinkaya, Erdogan; Ozbudak, Omer; Kilic, Talat; Demirci Ucsular, Fatma; Demirkol, Baris; Duman, Dildar; Karadeniz, Gulistan; Koksal, Nurhan; Soyler, Yasemin; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: Lung cancer is one of the significant comorbidities seen in patients with Idiopathic Pulmonary Fibrosis (IPF). However, there is limited data on non-IPF Pulmonary Fibrosis (PF) patients with lung cancer (LC). The present study aims to compare the characteristics and survival outcomes of patients diagnosed with LC in IPF and non-IPF PF.Methods: The multicenter data records of IPF and non-IPF PF patients diagnosed with lung cancer between 2010- 2022 were analyzed in this descriptive, cross-sectional, and retrospective study.Results: Of the 251 patients involved in this study [164 IPF-LC, 87 non-IPF PF-LC], 89.6% were male, the mean age was 69±7.9 years and the smoking rate was 85.7%. Honeycomb pattern was more frequently observed in IPF-LC patients [62.8%,37.9%p